BUDIDAYA JAMUR PERUSAK KAYU VI. BUDIDAYA PLEUROTUS OSTREATUS PADA DOLOK LIMA JENIS KAYU - Sihati Suprapti; Ginuk Sumarni (Pusat Penelitian dan Pengembangan Hasil Hutan, 1988)
Oyster mushroom (Pleurotus ostreatus) was cultivated on logs of five wood species, i.e. hamerang (Ficus grossularoides Burn.f.), jeungjing (Albizia falcataria (L.) Eosb.), jirak (Symplocos fasciculata Zoll.), kihuut (Vernonia arborea Ham.) and manii (Maesopsis eminii Engl.).The logs were kept in a house, at Gunung Bunder Forest Complex, Bogor (first experiment) and under soka trees in Bogor (second experiment).The logs start producing fungus two months after inoculation. After eight month observation, the highest yield per log was obtained from manii 1139.90 g (in a house) and 1171.62 g (under soka trees; and the lowest yield was on jirak (0.99 g). Total yield during the experiment per m of log, under soka trees was higher than that cultivated in a house Manii and hamerang logs probably belong to media for oyster mushroom than other species